Penerapan Konvensi Perlindungan Anak Den Haag Terhadap Kasus Anak dalam Keluarga Transnasional - Neli Zakiyatun Nufus; Elan Jaelani (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research explains the application of the Hague Child Protection Convention to cases of children in transnational families using normative juridical research methods, namely research that focuses on studying positive legal rules. In this case, it is indirect that research using normative juridical methods uses an approach to court decisions as an existing legal source. Or in another sense, this normative juridical method focuses on reviewing legal studies. As normative legal research, this research covers legal provisions, analysis of legal decisions with legal actions and the resulting legal consequences. The Hague Child Protection Convention permits the transfer of jurisdiction from authorities exercising jurisdiction based on their habitual residence or whereabouts to authorities in another Contracting State who may be “better placed in a particular case to assess the best interests of the child.” These jurisdictional provisions are largely consistent with US law, except for the approach to continuing jurisdiction in cases where the child acquires a new residence.